Optimization of Xylanase Production by Streptomyces costaricanus 45I-3 Using Various Substrates through Submerged Fermentation - SIPRIYADI SIPRIYADI; ARIS TRI WAHYUDI; MAGGY THENAWIDJAYA SUHARTONO; ANJA MERYANDINI (Indonesian Society for microbiology, 2020)
Xylanase is an important hydrolytic enzymes with many application in several industries, but to obtain enzyme derived products is not easy. Thus, the optimization of efficient xylanases production is a great interest for biotechnological application. This study aims to determine the type of substrate, medium composition, and optimum conditions of xylanase production by S. costaricanus 45I-3. Determination of substrate type was done by growing the tested bacteria on birchwood xylan, beechwood xylan, oat spelled xylan, corn cobs xylan, and tobacco xylan substrate, meanwhile the determination of medium composition and enzyme production were done by measuring xylanase activity at various substrate concentration and replacing the carbon, nitrogen, phosphate and surfactants source. The results showed that the highest enzymatic index (EI) produced from corn cob xylan substrate at 3.60 meanwhile the second highest was beechwood xylan substrate at 2.87 EI, however this substrate is purer, thus this substrate was selected and used as xylan sources for further optimization measurement. The best xylanase activity (2.29 U/mL) obtained on eighth day after inoculation on rotary incubator at 120 rpm in 28 ÂºC. Arabinose as the source of carbon generate the highest activity at 3.161 U/mL meanwhile the most preferred source of phosphate is Na2HPO4 (2.37 U/mL). Both source of nitrogen i.e. nitrogen ammonium sulphate (NH4)2SO4 and yeast extract were able to produce xylanase at 2.57 and 2.36 U/mL. The addition of surfactant in production medium showed addition of SDS surfactant (0.146 U/mL) and Tween 80 (0.438 U/mL) showed a negative response by decreasing the activity. The conclusion showed that the xylanase activity was increased after optimization at various C, N, and P sources, and the use of nitrogen source (NH4)2SO4), become a more economical alternative to replacing a nitrogen source yeast extract so it can lower the production costs of xylanase enzyme.